Проблеми розвитку інновацій в Україні - Ганечко, І. (Схід, 2011)
Стаття присвячена проблемам реалізації інноваційної діяльності вітчизняних компаній. Розглянуто обмежуючі чинники інноваційного розвитку в Україні. Обґрунтовано необхідність взаємовигідного партнерства держави та бізнесу, визначено напрями розвитку такого партнерства на сучасному етапі. In the article the problems of realization of innovative activity of domestic companies were described. Limiting factors of innovative development in Ukraine were considered. Necessity of mutually beneficial partnership of the state and business were grounded; directions of de velopment of such partnership on the modern stage were defined. In the article the problems of realization of innovative activity of domestic companies were described. Limiting factors of innovative development in Ukraine were considered. Necessity of mutually beneficial partnership of the state and business were grounded; directions of development of such partnership on the modern stage were defined.